Inhalatory and intravenous colistin in treating ventilator-associated pneumonia due to Acinetobacter species: should we combine them? - Matijašević, Jovan; Gavrilović, Srdjan; Andrijević, Ilija; Andrijević, Ana; Milić, Svetislava; Vukoja, Marija (Vojnosanitetski pregled, 2021)
Background/Aim. Acinetobacter is one of the most common causes of nosocomial infections, especially ventilator-associated pneumonia (VAP). Considering the increased presence of multidrug-resistant microorganisms and the lack of novel antibiotics, colistin merged as the last-resort antibiotic for life threatening nosocomial infections. Intravenous use of antibiotics is accepted as a gold standard for the treatment of pneumonia, but additional administration of inhaled antibiotics in the treatment of VAP has shown to be advantageous in some clinical trials. The aim of this study was to investigate the effect of inhalatory colistin as an adjunct to intravenous colistin on the survival of patients with VAP caused by Acinetobacter species. Methods. We conducted a retrospective study to evaluate the efficacy of combination of inhalatory and intravenous colistin vs. intravenous colistin alone in 69 patients in the Intensive Care Units (ICU) with VAP caused by Acinetobacter baumannii. The patients were treated in the ICU at the Institute for Pulmonary Diseases of Vojvodina, Sremska Kamenica (Serbia) in the period from January, 2013 to March, 2018. Baseline demographic data, severity of the disease, comorbidities, colistin regimen and length of the treatment were collected. The primary outcome was 28-day mortality. Results. Twenty seven of total 69 (39.1%) patients received combined intravenous and inhalatory colistin. Forty two (60.9%) patients received only intravenous colistin. Compared to the combined use of the drug (intravenous and inhalatory colistin), patients receiving intravenous colistin alone had a significantly increased risk of death during 28 days [25.9% vs. 61.9%, respectively; odds ratio (OR) 4.464, 95% confidence interval (CI) 1.539–2.925; p = 0.006]. Length of colistin use (> 7 days) was also associated with reduced survival (OR 0.22; 95% CI 0.080–0.606; p = 0.003). After adjusting for baseline severity of the illness (APACHE score) and length of colistin treatment, patients receiving only intravenous colistin had greater 28-day mortality rate compared to patients receiving both intravenous and inhalatory colistin (OR 6.305; 95% CI 1.795–22.153; p = 0.004). Conclusion. Our results suggest that adding inhalatory to intravenous colistin might be beneficial in the treatment of VAP caused by Acinetobacter species.
Keywords: pneumonia, ventilator-associated; acinetobacter; colistin; administration, inhalation; infusions, intravenous; treatment outcome